2017
DOI: 10.1111/cas.13441
|View full text |Cite
|
Sign up to set email alerts
|

Xanthohumol inhibits angiogenesis by suppressing nuclear factor‐κB activation in pancreatic cancer

Abstract: Xantohumol, a prenylated chalcone from hops (Humulus lupulus L.), has been shown to inhibit proliferation in some cancers. However, little is known regarding the effects of xanthohumol in pancreatic cancer. We have previously reported that activation of the transcription factor nuclear factor‐κB (NF‐κB) plays a key role in angiogenesis in pancreatic cancer. In this study, we investigated whether xanthohumol inhibited angiogenesis by blocking NF‐κB activation in pancreatic cancer in vitro and in vivo. We initia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
64
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(65 citation statements)
references
References 29 publications
1
64
0
Order By: Relevance
“…Ursolic acid from Ligustrum lucidum and the chemotherapeutic drug cisplatin, have been shown to inhibit cervical cancer cell growth through interfering with NF-κB signaling pathway via decreasing p65 level (Li et al, 2017a). Xanthohumol from Humulus lupulus L. was also shown to inhibit pancreatic cancer cell angiogenesis through interfering with this pathway (Saito et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Ursolic acid from Ligustrum lucidum and the chemotherapeutic drug cisplatin, have been shown to inhibit cervical cancer cell growth through interfering with NF-κB signaling pathway via decreasing p65 level (Li et al, 2017a). Xanthohumol from Humulus lupulus L. was also shown to inhibit pancreatic cancer cell angiogenesis through interfering with this pathway (Saito et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…A number of recent reports have shown that Xn could exert anticancer activities against various cancers such as leukemia [18], hepatocellular carcinoma [19], breast cancer [20,21], prostate cancer [22], colon cancer [23], and ovarian cancer [24]. This anticancer activity involves pleiotropic action on various signaling pathways, such as mitogen-activated protein kinase (MAPK) [25], mitochondria-and Bcl-2-related proteins (intrinsic apoptosis pathway) and the ligation of death receptors belonging to the tumor necrosis factor (TNF)-receptor superfamily (extrinsic apoptosis pathways) [26], and angiogenesis inhibition via the nuclear factor kappa B (NF-κB) pathway [27].…”
Section: Introductionmentioning
confidence: 99%
“…The extension of the vascular network is fundamental to assess the response to the treatment of anti-tumour drugs. Multiple authors use a microvessel density analysis system by CD31 expression in pancreatic PDX similar to ours[ 5 , 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%